Sexuality and HIV prevention: consensus and dissent of Catholic youths - Santos Couto, Pablo Luiz; Santos Paiva, Mirian; Freitas de Oliveira, Jeane; Tosoli Gomes, Antônio Marcos; Argolo Teixeira, Marizete; Teixeira Boa Sorte, Elionara (Investigación y Educación en Enfermería, 2018)
Objective. To analyze the consensus and dissent of Catholics youths about HIV/AIDS prevention from their representations about sexuality. Methods. This is a quantitative and qualitative research based on the Theory of Social Representations carried out with 84 Catholics youths who answered online to the Free Word Association Test on Facebook and three questions about the influence of Catholic doctrine on the free exercise of sexuality and the adoption of practice safe sex. The techniques of Factorial Analysis of Correspondence and Semantic Content were used. Results. On sexuality, only the young women with access to higher education represented the term as a free practice that should not lead to guilt. There was a consensus on chastity, virginity, and sex within marriage as effective means of HIV prevention. It is also representational consensus of the young people that sexual practice is pleasurable, however, condemned by the church, and that AIDS is a preventable disease. Social representations have revealed dissent between men and women, while they consider that the exercise of sexuality should be restricted to marriage, they advocate sexual freedom. As for AIDS, they represent that the syndrome stems from prejudice, and they consider that vulnerability favors contagion. Conclusion. In the consensuses among the young people studied, there are sexist prejudices and stereotypes that influence HIV/AIDS prevention actions. Therefore, health professionals, especially those of Nursing should propose actions aimed at this age group in educational activities about the adoption of preventive practices on safe sex, always considering the social representations around the subject. How to cite this article: . Couto PLS, Paiva MS, Oliveira JF, Gomes AMT, Teixeira MA, Sorte ETB. Sexuality and HIV prevention: consensus and dissent of Catholic youths. Invest. Educ. Enferm. 2018; 36(2):e06.